Improving smallholder farming systems in Imperata areas of Southeast Asia: alternatives to shifting cultivation - Menz, K.; Magcale-Macandog, D.; Rusastra, I.W. (Australian Centre for International Agricultural Research, 1998)
This is a report of a collaborative research project, 'Improving smallholder farming systems in Imperata areas of Southeast Asia: a bioeconomic modelling approach' sponsored by the Center for international Forestry Research and the Australian Centre for International Research. The nature of the Imperata problem and the methodology is outlined. Imperata is essentially restricted to upland areas, since it does not coexist with lowland rice farming. There is a section on bioeconomic analysis of traditional smallholder 'shifting cultivation' farming systems where the fallow is Imperata and another contains a series of case study descriptions of successful tree growing by smallholders on Imperata grasslands. The core modelling work of the project is reported. Various tree-based interventions are modelled with and without an animal component. Some of these modelled farming systems are already in place in farmers' fields. In these cases, possible management or policy interventions analysed with the models can point the way to productive and economic improvements. In other cases, the farming systems modelled are 'experimental' in nature. Imperata grows on uplands of various slopes, but some special attention is given to Imperata on steeply sloping land where soil erosion is a particular problem. Finally, two key issues in relation to tree growing on Imperata grassland, fire control and carbon sequestration, are addressed. These are viewed both from the viewpoints of the individual smallholder and of the broader society. This is an overview and compilation of studies, many of which were previously reported in a series of project papers published by Centre for Resource and Environmental Studies, Australian National University between 1995 and 1998.